Legal Analysis of Investment in the Palm Oil Sector in Indonesia - Mia Kinasih; Gotlif P Pasaribu (Jurnal Kajian Ilmu Hukum, 2026)
ndonesia's palm oil industry plays a strategic role in national economic development by attracting investment, generating employment, and contributing significantly to export revenues. However, the sector continues to face persistent legal challenges, including overlapping land tenure, agrarian conflicts, environmental degradation, and regulatory inconsistencies that undermine legal certainty and sustainable investment. This study aims to examine the legal framework governing investment in Indonesia's palm oil sector, identify the major legal issues affecting its implementation, and analyze the legal protection mechanisms that support sustainable investment governance. The research employs a normative legal approach using statutory, conceptual, and analytical methods. Data were collected from primary legal materials, secondary legal literature, judicial decisions, and relevant policy documents, and analyzed through qualitative juridical interpretation. The findings reveal that Indonesia has established a comprehensive regulatory framework through investment, agrarian, plantation, environmental, and business licensing laws. Nevertheless, the effectiveness of these regulations remains constrained by fragmented institutional governance, overlapping legal authorities, and inconsistent implementation across sectors. The study further finds that legal certainty in palm oil investment depends not only on regulatory completeness but also on the harmonization of legal institutions responsible for land administration, environmental governance, and investment supervision. This research proposes the concept of Integrated Legal Governance, which combines legal certainty, legal protection, and sustainable development principles as a comprehensive framework for strengthening investment governance. The study contributes to the advancement of investment law by demonstrating that institutional harmonization is the key determinant of sustainable palm oil investment and provides policy recommendations for regulatory integration, environmental governance, and the protection of investors and indigenous communities in Indonesia